Anticandidal activity of cobalt containing sunflower oil‐based polymer. Issue 12 (2nd April 2013) - Singh, Taruna; Khan, Nazia Umar; Shreaz, Sheikh; Hashmi, Athar Adil
<x xml:space="preserve">Abstract</x> Bioactive metal cobalt containing sunflower oil‐based polyesteramide resin was developed by condensation polymerization reaction among oil‐derived sunflower fatty amide diol, adipic acid, and cobalt chloride. Microwave‐assisted synthesis was used throughout the reaction as it enhances reaction rate, gives higher yield, and greater purity of the products. Spectroscopic techniques, such as Fourier transform infrared spectroscopy and proton‐nuclear magnetic resonance, have been used to establish the structure of the polymers. Presence of cobalt in polymer has been confirmed through atomic absorption spectroscopy. Standard laboratory methods such as acid value, hydroxyl value, saponification value, iodine value, specific gravity, and viscosity were used to study the physicochemical characteristics of the polymers. Thermal behavior of the polymer was analyzed using thermogravimetry/differential thermal analysis. The synthesized polymers were evaluated for their biological activity. This study indicates that the synthesized polymer has significant antifungal activity against Candida, including azole‐resistant strains, advocating further investigation for clinical applications in the treatment of fungal infections. POLYM. ENG. SCI., 53:2650–2658, 2013. © 2013 Society of Plastics Engineers